“Um fã teu, quem realmente te admira, jamais faria esse tipo de coisa”: On the existence of appositive free relatives in Brazilian Portuguese - Medeiros Junior, Paulo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
Brazilian Portuguese data provide evidence to the claim I make in this paper that there are appositive free relatives, contrary to what Emonds (1979) states, for whom free relatives cannot have appositive semantics or syntax. I argue there are reasons to believe the wh-sentence evidenced in the title of this paper is in fact a free relative that carries appositive content, considering issues such as distribution, matching, the nature of quem and semantic content. The quem-type sentence I put into analysis in the present paper differs from an ordinary (headed) appositive relative clause for it seems to be juxtaposed to the nominal it relates to, being equivalent to it, a condition that leads to the impossibility of a relativization process in Kaynes’s (1994) terms for the derivation of this kind of sentence.